Microbiota and body axes as a new therapeutic approach in precision medicine - Burgos-Molina, Antonio Manuel; González Vidal, Alejandro; Alamilla Presuel, Juan Carlos; Mercado-Sáenz, Silvia; Ruiz-Gómez, Miguel José (My University, 2022)
There is a marked relationship between the composition and diversity of the microbiota and various diseases distant from the intestine. This relationship occurs through different body axes between the intestine and the eye, brain, liver, bone, kidney and hormonal system. A correct action on dysbiosis can lead to a better response to the treatment of diseases in these organs. This new therapeutic approach is of great interest for precision medicine.
Keywords: Cáncer - Tratamiento; Microbiota diversity; Dysbiosis; Corporal/Body axes; Precision medicine